2019
DOI: 10.1051/0004-6361/201936447
|View full text |Cite
|
Sign up to set email alerts
|

First imaging spectroscopy observations of solar drift pair bursts

Abstract: Drift pairs are an unusual and puzzling type of fine structure sometimes observed in dynamic spectra of solar radio emission. They appear as two identical short narrowband drifting stripes separated in time; both positive and negative frequency drifts are observed. Currently, due to the lack of imaging observations, there is no satisfactory explanation for this phenomenon. Using the Low Frequency Array (LOFAR), we report unique observations of a cluster of drift pair bursts in the frequency range of 30 − 70 MH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, the duration of spikes near 30 MHz are shorter up to a factor of ∼20. The observed spike areas decrease with increasing frequency from 297 to 122 arcmin 2 between 30 and 45 MHz (Figure 4(f)) in a similar manner to drift-pair bursts (Kuznetsov & Kontar 2019), and is approximated with a power law A ∼ f −γ where γ = 2.3 and 1.9 for spikes and striae, respectively. The large uncertainties are due to their low intensities.…”
Section: Spike Characteristicsmentioning
confidence: 62%
“…However, the duration of spikes near 30 MHz are shorter up to a factor of ∼20. The observed spike areas decrease with increasing frequency from 297 to 122 arcmin 2 between 30 and 45 MHz (Figure 4(f)) in a similar manner to drift-pair bursts (Kuznetsov & Kontar 2019), and is approximated with a power law A ∼ f −γ where γ = 2.3 and 1.9 for spikes and striae, respectively. The large uncertainties are due to their low intensities.…”
Section: Spike Characteristicsmentioning
confidence: 62%
“…The simulations in Kuznetsov et al (2020) show that sources observed away from the disk center can present superluminal centroid velocities, as was observed for striae (Zhang et al 2020) and spikes (Clarkson et al 2021). If the source motion is nonradial, then sources closer to the disk center can also present speeds near c, as observed by drift-pair bursts (Kuznetsov & Kontar 2019).…”
Section: Introductionmentioning
confidence: 95%
“…In comparison, the bulk Type IIIb structures shown in Figure 2(b,e) have drift rates of −3.14±0.21 and −2.31±0.26 MHz/s, respectively, measured by a linear fit to the peak flux position at the central frequency of each striae.The observed spike FWHM area at the peak of the central frequency is 202.19 ± 16.3 arcmin 2 at 34.5 MHz (Figure3(d)). The observed spike areas decrease with increasing frequency from 297 to 122 arcmin 2 between 30 to 45 MHz (Figure4(f)) in a similar manner to driftpair bursts(Kuznetsov & Kontar 2019), and is approximated with a power law A ∼ f −γ where γ = 2.3 and 1.9 for spikes and striae, respectively. The large uncertainties are due to their low intensities.…”
mentioning
confidence: 65%